2014
DOI: 10.1163/15685411-00002791
|View full text |Cite
|
Sign up to set email alerts
|

Parasitodiplogaster species associated with Pharmacosycea figs in Panama

Abstract: Parasitodiplogaster species that are associated with figs in the Ficus subsection Pharmacosycea, i.e., Ficus maxima, F. yoponensis, F. insipida and F. glabrata, were studied using morphological characters and molecular sequences. Some nematodes isolated from the fig sycones were casually observed and recorded as morphospecies according to their morphotype, and were then digested for their DNA, while others were fixed in formalin-glycerin for additional morphological study. High resolution microscopic observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
(21 reference statements)
1
20
0
Order By: Relevance
“…One striking example is the group of fig‐associated nematodes that enter the fig syconium through their tight association with fig wasps, and which is characterized by an extraordinary co‐evolution among figs, fig wasps and nematodes. Particularly, Teratodiplogaster and Parasitodiplogaster were shown to co‐evolve with a large number of figs and fig wasp species (Kanzaki et al ., ). More recently, the complexity of nematodes associated with figs and fig wasp has been extended as members of two other diplogastrid nematode genera, Pristionchus and Acrostichus , were found to also co‐evolve in the fig ecosystem (Susoy et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…One striking example is the group of fig‐associated nematodes that enter the fig syconium through their tight association with fig wasps, and which is characterized by an extraordinary co‐evolution among figs, fig wasps and nematodes. Particularly, Teratodiplogaster and Parasitodiplogaster were shown to co‐evolve with a large number of figs and fig wasp species (Kanzaki et al ., ). More recently, the complexity of nematodes associated with figs and fig wasp has been extended as members of two other diplogastrid nematode genera, Pristionchus and Acrostichus , were found to also co‐evolve in the fig ecosystem (Susoy et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…After considering the morphological characters, i.e., no clear synapomophy can be found for these two genera, the sep aration of Parasitodiplogaster seems reasonable. Several characteristic stomatal morphologies and other typologi cal characters have been reported recently (Giblin-Davis et al, 2006;Bartholomaeus et al, 2009;Kanzaki et al, 2009Kanzaki et al, , 2010Kanzaki et al, , 2012Kanzaki et al, , 2014bWohr et al, 2014), and these characterise the species groups of Parasitodiplo gaster. Detailed morphological and phylogenetic compar isons followed by generic-level taxonomic analysis will be necessary to resolve these issues.…”
Section: Phylogenetic Relationship and Taxonomymentioning
confidence: 76%
“…Teratodiplogaster belongs to a clade including Al lodiplogaster, Parasitodiplogaster, and Teratodiplogaster (e.g., Kanzaki et al, 2011Kanzaki et al, , 2013aKanzaki et al, , 2014b. The recep taculum seminis found in T. martini and T. variegatae n. sp.…”
Section: Morphological Charactersmentioning
confidence: 99%
“…Martin et al (1973) reported a variety of different ne matode types associated with figs in tropical Africa, but provided few taxonomic details. Two nematode genera, Schistonchus Cobb, 1927(Fuchs, 1937) (Aphelenchoididae) and Parasitodiplogaster Poinar, 1979 (Diplogastridae), are well known from inside the sycones of Ficus species worldwide (Gasparrini, 1864;Poinar, 1979;Kumari & Reddy, 1984;Reddy & Rao, 1984;Poinar & Herre, 1991;Giblin-Davis et al, 1995, 2003, 2006Lloyd & Davies, 1997;DeCrappeo & Giblin-Davis, 2001;Anand, 2002;Zeng et al, 2007Zeng et al, , 2010Zeng et al, , 2011Zeng et al, , 2013aBartholomaeus et al, 2009Bartholomaeus et al, , 2012Davies et al, 2009Davies et al, , 2010Kanzaki et al, 2010Kanzaki et al, , 2012Kanzaki et al, , 2013Kanzaki et al, , 2014aWohr et al, 2014). Schistonchus is a polyphyletic plant-parasitic nematode grouping in the Aphelenchoididae that feeds and reproduces on the epidermis of florets inside the sycone and is an internal phoretic of its fig wasp pol linator host which transports it to the next suitable fig (Vovlas etal., 1992(Vovlas etal., , 1996Giblin-Davis etal., 1995;Cen ter et al, 1999;Davies et al, 2010).…”
mentioning
confidence: 99%
“…Parasitodiplogaster is an apparently parasitic or possi bly necromenic nematode associate that develops in its fig wasp pollinator host before leaving to mate and pro duce infective juveniles inside the fig that infect the next generation of wasps as they leave for a new fig (Poinar & Herre, 1991;Giblin-Davis et al, 1995, 2006Kan zaki et al, 2010Kan zaki et al, , 2012Kan zaki et al, , 2013Kan zaki et al, , 2014a. There are currently 15 described Parasitodiplogaster species (Kanzaki et al, 2014a). In addition, the diplogastrids Teratodiplogaster Kanzaki, Giblin-Davis, Ye, Center & Thomas, 2009(Kan zaki et al, 2009 and Rhabditolaimus Fuchs, 1914 (= Myctolaimus and Ceratosolenus) have been reported from Ficus racemosa L. and figs of the subgenus Sycomorus (Anand, 2005(Anand, , 2006Kanzaki et al, 2006), and the rhabditid Caenorhabditis briggsae (Dougherty & Nigon, 1949) Dougherty, 1953 has been reported from rotting figs (Kiontke et al, 2011), while other undescribed species of the latter genus have also been observed in early phase figs (Kanzaki, unpubl.…”
mentioning
confidence: 99%